Dakwah Digital dan Moderasi Beragama Perspektif Akademisi vs Salafy Pada Kanal Youtube FUAD TV dan Rodja TV - Zulfiyani Sudirman (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2025)
This research is motivated by the growing growth of digital da'wah through social media, particularly YouTube, which has become a strategic platform for the dissemination of religious thought in Indonesia. In a multicultural society, the concept of religious moderation is a crucial issue because it plays a role in maintaining tolerance, unity, and a harmonious social life. However, the interpretation of religious moderation is not always uniform. Differences in perspectives between academics and Salafist groups have given rise to diverse narratives that have developed in the digital space, making them interesting for comparative study. This study aims to analyze the similarities and differences in perspectives on religious moderation conveyed through the YouTube channels FUAD TV, representing academics, and Rodja TV, representing Salafist da'wah. The study employed a qualitative descriptive method with a comparative approach. Data were collected through observation of videos discussing religious moderation, analysis of lecture transcripts, and documentation studies from various relevant scientific literature. Data were analyzed using content analysis techniques to identify themes, argumentation patterns, and characteristics of da'wah delivery on each channel. The results of this study indicate that the academic perspective on FUAD TV tends to prioritize an inclusive, dialogical, and contextual approach in understanding Islamic teachings and interfaith relations. In contrast, Rodja TV emphasizes a textual and normative approach with tolerance boundaries based on a literal understanding of the Qur'an and Hadith. Despite differences in methodological and interpretive approaches, both perspectives reject extremism, violence, and actions that threaten national unity. This research contributes to enriching the study of digital da'wah and offers a more comprehensive understanding of the implementation of religious moderation amidst the dynamics of pluralistic Indonesian society and the ever-evolving digital communication era. Abstrak Penelitian ini dilatarbelakangi oleh semakin berkembangnya dakwah digital melalui media sosial, khususnya YouTube, yang menjadi ruang strategis dalam penyebaran pemikiran keagamaan di Indonesia. Di tengah masyarakat yang multikultural, konsep moderasi beragama menjadi isu penting karena berperan dalam menjaga toleransi, persatuan, dan kehidupan sosial yang harmonis. Namun, pemaknaan terhadap moderasi beragama tidak selalu seragam. Perbedaan cara pandang antara kalangan akademisi dan kelompok Salafy memunculkan beragam narasi yang berkembang di ruang digital, sehingga menarik untuk dikaji secara komparatif. Penelitian ini bertujuan menganalisis persamaan dan perbedaan perspektif moderasi beragama yang disampaikan melalui kanal YouTube FUAD TV sebagai representasi kalangan akademisi dan Rodja TV sebagai representasi dakwah Salafy. Penelitian menggunakan metode deskriptif kualitatif dengan pendekatan komparatif. Data dikumpulkan melalui observasi terhadap video-video yang membahas moderasi beragama, analisis transkrip ceramah, serta studi dokumentasi dari berbagai literatur ilmiah yang relevan. Data dianalisis menggunakan teknik analisis isi untuk mengidentifikasi tema, pola argumentasi, dan karakteristik penyampaian dakwah pada masing-masing kanal. Hasil penelitian menunjukkan bahwa perspektif akademisi pada FUAD TV cenderung mengedepankan pendekatan inklusif, dialogis, dan kontekstual dalam memahami ajaran Islam serta hubungan antarumat beragama. Sebaliknya, Rodja TV lebih menekankan pendekatan tekstual dan normatif dengan batasan toleransi yang didasarkan pada pemahaman literal terhadap Al-Qur'an dan hadis. Meskipun terdapat perbedaan dalam pendekatan metodologis dan penafsiran, kedua perspektif sama-sama menolak ekstremisme, kekerasan, dan tindakan yang mengancam persatuan bangsa. Penelitian ini memberikan kontribusi dalam memperkaya kajian dakwah digital serta menawarkan pemahaman yang lebih komprehensif mengenai implementasi moderasi beragama di tengah dinamika masyarakat Indonesia yang plural dan era komunikasi digital yang terus berkembang.